Rancang Bangun Urine Analyzer Pendeteksi Dini Indikasi Penyakit Diabetes Melitus - Edo Daryono; Imam Tri Harsoyo; Bayu Wahyudi (Unversitas Muhammadiyah Mataram, 2025)
Abstract: This research aims to design and develop a microcontroller- based Urine Analyzer capable of early detection of diabetes mellitus indications through Urine color analysis. The device utilizes a TCS3200 color sensor to process RGB light intensity and identify glucose levels in Urine. Testing was conducted on four Urine samples, with five tests per sample, resulting in a total of 20 trials. The device achieved an accuracy rate of 90%, with 18 results matching the readings of a commercial analyzer. The two errors detected were attributed to variations in light intensity and the quality of test strips. This device demonstrates reliable detection capabilities and has the potential to become a portable and cost- effective solution for early diabetes mellitus detection. Further development, such as improving sensor stability and algorithm accuracy, is expected to enhance the overall performance of the device.Abstrak: Penelitian ini bertujuan untuk merancang dan mengembangkan alat Urine Analyzer berbasis mikrokontroler yang mampu mendeteksi dini indikasi penyakit diabetes melitus melalui analisis warna Urine. Perangkat ini menggunakan sensor warna TCS3200 yang memproses intensitas cahaya RGB untuk mengidentifikasi kadar gula dalam Urine. Uji coba dilakukan pada empat sampel Urine dengan masing-masing lima pengujian, menghasilkan total 20 percobaan. Tingkat akurasi alat mencapai 90%, di mana 18 hasil sesuai dengan pembacaan alat pabrikan. Dua kesalahan yang ditemukan disebabkan oleh variasi intensitas cahaya dan kualitas strip uji. Alat ini menunjukkan kemampuan deteksi yang andal dan berpotensi menjadi solusi portabel dan hemat biaya untuk mendukung deteksi dini diabetes melitus. Pengembangan lebih lanjut, seperti peningkatan stabilitas sensor dan akurasi algoritma, diharapkan dapat meningkatkan kinerja alat secara keseluruhan.